Serum CA19-9 and CEA levels, Serum CAT, GSH, oxidized glutathione levels , 8-dihidro-2′-deoxiguanosina and F2-Isoprostanes levels in colorectal cancer patients with Lactobacillus: A randomized double-blind controlled trial - Chen, Shiru; Ning, Weili; Zhang, Jiye; Wu, Zhenting; Zhou, Hang; Liu, Ying (Journal of Medical Biochemistry, 2025)
Background: Oxidative stress (OS) plays a crucial role in colorectal cancer (CRC) progression. Lactobacillus has been proposed as a potential modulator of OS. This randomized controlled trial aimed to evaluate the effects of Lactobacillus supplementation on OS markers and its related signaling pathways in CRC patients after surgery. Methods: A total of 76 CRC patients were enrolled and randomized into two groups: the study group (n=39) received Lactobacillus supplementation, while the control group (n=37) received a placebo. The intervention lasted for six months following surgery. Serum levels of catalase (CAT), glutathione (GSH), oxidized glutathione (GSSG), 8-oxo-7,8-dihydro-2′-deoxyguanosine (8-oxodG), and F2-isoprostanes (F2-IsoPs) were measured. In addition, the NRF2/KEAP1, p38 MAPK, and JNK signaling pathways were assessed via western blot analysis. Results: Following Lactobacillus supplementation, serum CEA levels significantly decreased, whereas CA19-9 levels remained unchanged. OS marker analysis demonstrated increased CAT, GSH, and F2-IsoPs levels and decreased GSSG and 8-oxodG levels in the study group compared to the control group. Western blot results revealed that NRF2, ASK1, MKK3, p-p38, and MKK4 protein levels were significantly reduced after Lactobacillus intervention, while KEAP1 and p-JNK remained unchanged. Conclusions: Oral administration of Lactobacillus for six months reduced OS marker levels and inhibited NRF2/KEAP1, p38 MAPK, and JNK signaling pathways in CRC patients after surgery. These findings suggest that Lactobacillus may contribute to CRC management by modulating oxidative stress.